Validity and reliability of a wearable blood flow restriction training device for arterial occlusion pressure assessment - Zhang, Wei-Yang; Zhuang, Shu-Can; Chen, Yuan-Ming; Wang, Hao-Nan (Frontiers in Physiology, 2024)
The blood flow restriction (BFR) training is an effective approach to promoting muscle strength, muscle hypertrophy, and regulating the peripheral vascular system. It is recommended to use to the percentage of individual arterial occlusion pressure (AOP) to ensure safety and effectiveness. The gold standard method for assessing arterial occlusive disease is typically measured using Doppler ultrasound. However, its high cost and limited accessibility restrict its use in clinical and practical applications. A novel wearable BFR training device (Airbands) with automatic AOP assessment provides an alternative solution. This study aims to examine the reliability and validity of the wearable BFR training device.Methods: Ninety-two participants (46 female and 46 male) were recruited for this study. Participants were positioned in the supine position with the wearable BFR training device placed on the proximal portion of the right thigh. AOP was measured automatically by the software program and manually by gradually increasing the pressure until the pulse was no longer detected by color Doppler ultrasound, respectively. Validity, inter-rater reliability, and test-retest reliability were assessed by intraclass correlation coefficients (ICC) and Bland-Altman analysis.The wearable BFR training device demonstrated good validity (ICC = 0.85, mean difference = 4.1 ± 13.8 mmHg [95% CI: -23.0 to 31.2]), excellent inter-rater reliability (ICC = 0.97, mean difference = -1.4 ± 6.7 mmHg [95% CI: -14.4 to 11.7]), and excellent test-retest reliability (ICC = 0.94, mean difference = 0.6 ± 8.6 mmHg [95% CI: -16.3 to 17.5]) for the assessment of AOP. These results were robust in both male and female subgroups.The wearable BFR training device can be used as a valid and reliable tool to assess the AOP of the lower limb in the supine position during BFR training.